Self-Concept of Makeup Enthusiast Female Students in a Beauty Brand Community: Pinkflash (Universitas Terbuka, 2025)
This study explores the self-concept of female university students who are makeup enthusiasts and active members of the Pinkflash Community, a brand-led beauty group operating primarily through Telegram and Instagram. The research adopts a qualitative phenomenological approach to uncover participants’ live experiences and the meanings they assign to their community engagement. Guided by Calhoun and Acocella’s self-concept theory, McCall and Simmons’ identity theory, and Alfred Schutz’s phenomenology, the study examines three core dimensions of self-concept—knowledge, expectations, and evaluation—alongside because motives and in-order-to motives. Data were collected through in-depth interviews with three purposively selected participants, non-participant observation of community activities, and document analysis of community-generated content. The findings reveal that participation in the Pinkflash Community enhances members’ self-awareness as beauty enthusiasts (knowledge), fosters professional aspirations such as becoming makeup artists or influencers (expectations), and promotes continuous self-assessment through peer feedback and personal goal tracking (evaluation). Symbolic elements, including the community’s pink aesthetic and the “Pinkiedolls” identity label, reinforce a shared sense of belonging. The study concludes that the Pinkflash Community functions both as a social support system and a professional development platform, enabling members to negotiate personal identity within the context of global beauty trends and local cultural values. These findings contribute to the understanding of digital brand communities as hybrid spaces that simultaneously fulfils social, commercial, and identity-related functions. Practical implications highlight the importance for brands to foster participatory and supportive environments that align with members’ personal and professional goals.